Tipos y motivos épicos: los poemas homéricos y el Cantar de mio Cid en paralelo - Alberto Montaner Frutos (Atalaya)
This paper explores the parallels between the Song of the Cid and the Homeric poems with focus on two specific aspects. First the essay analyzes the character of aristocratic miles gloriosus represented by Paris in the Iliad and the Infantes de Carrión and the Count of Barcelona in the Song of the Cid. Then, the fasting out of spite performed by Ulysses in the Odyssey and by the Count of Barcelona in the Castilian poem is analyzed. The paper concludes by emphasizing the importance of addressing these cases in terms of literary isomorphism and not as direct sources.